Contribution of food groups to energy, grams and nutrients-to-limit: the Latin American Study of Nutrition and Health/Estudio Latino Americano de Nutrición y Salud (ELANS) - Fisberg, Regina Mara (2021)
Objective: To quantify the energy, nutrients-to-limit and total gram amount consumed and identify their top food sources consumed by Latin Americans. Design: Data from the Latin American Study of Nutrition and Health (ELANS). Setting: ELANS is a cross-sectional study representative of eight Latin American countries: Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru and Venezuela. Participants: Two 24-h dietary recalls on non-consecutive days were used to estimate usual dietary intake of 9218 participants with ages between 15-65 years. 'What We Eat in America' food classification system developed by United States Department of Agriculture was adapted and used to classify all food items consumed by the ELANS population. Food sources of energy, added sugars, SFA, Na and total gram amount consumed were identified and ranked based on percentage of contribution to intake of total amount. Results: Three-highest ranked food categories of total energy consumed were: rice (10·3%), yeast breads (6·9%), and turnovers and other grain-based items (6·8 %). Highest ranked food sources of total gram amount consumed were fruit drinks (9·6%), other 100% juice (9·3%) and rice (8·3%). Three highest ranked sources for added sugars were other 100% juice (24·1 %), fruit drinks (16·5%), and sugar and honey (12·4%). SFA ranked foods were turnovers and other grain-based (12·6 %), cheese (11·9%), and pizza (10·3%). Three top sources of Na were rice (13·9%), soups (9·1 %) and rice mixed dishes (7·3 %). Conclusion: Identification of top sources of energy and nutrients-to-limit among Latin Americans is critical for designing strategies to help them meet nutrient recommendations within energy needs.